Iran in the conflict of interests of Britain and the Soviet Union(The attack of August 25, 1941, for example) - Kamal, Asst.Prof.Dr. Hawar Kamal Mirza Abdullah; حمەكریم, سەرباز حمەكریم مصطفی (Sulaimani Journal for Humanities, 2025)
From the beginning of World War II, Iran had an important position for the Great Powers. Especially Britain and later the Soviet Union viewed Germany's activities in Iran as a serious threat to their interests and warned of their expulsion, but this went unanswered, leading to military attacks on Iran, Britain in the south and the Soviet Union in the north. With the expected attack, Iran fell under the domination of the occupation of the Great Powers and temporarily the two powers put aside their conflicts and brought together the interests and elimination of the threat of the Germans. But with the attack, Iran became the focus of the first Cold War conflict, which had secretly resumed immediately after the invasion. Analytical descriptive method is followed in this paper. The research consists of three topics: the first topic focuses on the struggle for British-Russian (Soviet) hegemony in Iran until 1941, the second topic emphasizes the motives and reasons behind the conflict of British and Soviet interests in Iran before the August 1941 invasion In the face of the occupation attack by British and Soviet forces on August 25, 1941 and the consequences of that attack.
Keywords: Iran; Britain; Soviet Union; Conflict of Powers in Iran; Occupation of Iran September 1941